Epithelial development in the forestomach of pasture-fed lambs (birth to 8 weeks) : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Veterinary Science at Massey University, New Zealand - Ilio, Kenneth Yerro (Massey University, 1983)
The histology, mitotic index, ultrastructure and Na+-K+-ATPase cytochemistry of lambs reared on pasture were studied during the period of weaning. Two embalmed mature non-pregnant Romney cross-brGd ewes and thirty Romney-cross lambs reared on Massey University sheep farms pastures were used. Five lambs {three in 1981 and two in 1982) were taken from their dams on pasture at each of the following respective ages: within 24 hours of birth, and at 12, 23, 34, 45 and 56 days. Stomach-tissue samples from 1 adult and from the lambs reared during the 1981 lambing season were prepared for histology using Haenatoxylin and Eosin, Nasson's green trichrome, Periodic-acid-Schiff and Toluidine Blue stains, and for conventional transmission electron microscopy. Tissue samples from the rumens of lambs reared during the 1982 season were used for strontium-capture technique Na+-K+-ATPase cytochemistry . Gross dissection o£ the stomach of one-day-old lambs confirmed that the largest compartment at birth is the abomasum, followed, in decreasing order of size; by the rumen, reticulum and omasum. Progressive development resulted in the forestomach compartments assuming their adult proportions by 56 days of age. Preliminary histological studies of epithelium taken from the rumen, reticulum, omasum and reticular groove of the adult sheep c0nfirmed it to be a stratified keratinizing epithelium. Five general cell layers were clearly seen: stratum basa1e, stratum spinosum, stratum granulosum, stratus transiticnale and stratum corneum. (In previous studies, the stratum granulosun and the stratum transitionale have been considered as one layer.) Mucopolysaccharides were located in the inter- cellular spaces in the stratum corneum. It is concluded that the ultrastructural features and Na+-K+-ATPase cytochemistry of the epithelium at 12 days of age appeared to be similar to those found in older animals. However, structural (and presumably functional) maturity did not appear to be complete until after 45 days of age at which stage the stratum transi- tionale had become complete and the mitotic index and the thickness of the epithelium had become stable. The increase of non-keratinocytes suggests the increasing immunocompetence of the epithelium. Tight junctions and extruded contents of membrane- coating granules in the intercellular spaces of the stratum corneum could provide a barrier to the diffusion of solutes across the epithelium. The development of gap junctions and the presence of Na+-K+-ATPase enzymatic sites in the membranes are consistent with the absorptive and transport functions of the epithelium, particularly the active transepithelial movement of sodium ions. Future studies could well show hormones, hormone-like substances and antibiotics to be important in the development of the forestomach epithelium in ruminants.
Keywords: Lambs; Epithelium